2014
DOI: 10.1371/journal.pone.0097235
|View full text |Cite|
|
Sign up to set email alerts
|

Diffusion Boundary Layers Ameliorate the Negative Effects of Ocean Acidification on the Temperate Coralline Macroalga Arthrocardia corymbosa

Abstract: Anthropogenically-modulated reductions in pH, termed ocean acidification, could pose a major threat to the physiological performance, stocks, and biodiversity of calcifiers and may devalue their ecosystem services. Recent debate has focussed on the need to develop approaches to arrest the potential negative impacts of ocean acidification on ecosystems dominated by calcareous organisms. In this study, we demonstrate the role of a discrete (i.e. diffusion) boundary layer (DBL), formed at the surface of some calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 92 publications
2
128
1
Order By: Relevance
“…When testing for the effect of flow speed on the coral -turf interactions, we found that increased flow reduces DBL thickness and oxygen extremes at the coral -algae interface. Increased flow commonly results in thinner DBLs [56,59]. Previous studies showed that high flow reduces algal competitiveness over corals and bacterial concentrations at the coral -algal interaction zone [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…When testing for the effect of flow speed on the coral -turf interactions, we found that increased flow reduces DBL thickness and oxygen extremes at the coral -algae interface. Increased flow commonly results in thinner DBLs [56,59]. Previous studies showed that high flow reduces algal competitiveness over corals and bacterial concentrations at the coral -algal interaction zone [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to create ecologically relevant flow conditions in the flumes is likely to be especially important for establishing ecological relevance, as flow is critical in modulating mass transfer and metabolism of coral reef organisms (Atkinson and Gilmer, 1992;Carpenter and Williams, 2007;Comeau et al, 2014c). In the case of stony corals, for example, high flow speeds are suspected to enhance coral calcification by favoring proton export from coral tissue through boundary layers (Jokiel, 2011;Jokiel et al, 2014); for coralline algae, high flow speeds might increase sensitivity to OA by reducing the capacity to maintain high pH in the diffusion boundary layer adjacent to the algal thallus (Cornwall et al, 2013(Cornwall et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Biogenic fluctuations (e.g. pH, O 2 ) at different temporal and spatial scale will produce alternating phases of adverse versus benign conditions which may buffer or amplify the impact of a stressor (Cornwall et al 2014).…”
Section: Synthesis and Conclusionmentioning
confidence: 99%